Fixed-term contracts and dismissal protection: Evidence from a policy reform in Germany - Lutz Bellmann; Hans-Dieter Gerner; Christian Hohendanner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2014)
In our paper, we analyze the impact of German employment protection legislation on the firms' employment adjustment patterns. We explore a reform of the Protection Against Dismissal Act (PADA) in 2004 that decreased the employment protection in small establishments and thus generated a quasi-experiment. Extending previous studies we distinguish between open-ended and fixed-term contracts, as the latter might be used to circumvent the PADA. Difference-in-differences estimations based on IAB Establishment Panel data show no overall effect of the reform on firms' employment adjustment patterns. However, the proportion of hirings based on fixed-term contracts decreases.
Keywords: 330